ADAPTED NEURO MANAGEMENT AND INTEGRAL METHODOLOGY IN DECISION EVALUATION. CUM INTERVENTION - S Sandhya; Jyotirmaya Satpathy (Agora International Journal of Economical Sciences)
With the advent of Management and Technology, the World is witnessing a plethora of problems; mental issues occupying the prime spot. This provides an opportunity for the discipline of adaptive neuromanagement and integrated methodologies to offer a ‘way out’; for those afflicted with mental issues. Based on the protocol evaluations obtained through Adapted Neuromanagement, this paper applies a variety of personalized intervention techniques oriented from the neurointegral methodology. These techniques inc lude; intervention with neurofeedback and biofeedback, personalized training programs to improve neuronal and physiological self regulation. mindfulness and relaxation techniques, implementation of specific protocols to reduce stress and improve attention, adapted to individual needs virtual reality exposure therapy, development and application of personalized scenarios to treat phobias, anxiety and ptsd, cognitive performance training based on computational interface, implementation of adaptive programs to improve specific executive and cognitive functions, based on the individual neurocognitive profile, qualitative neuropsychological training, implementation of rehabilitation and neuropsychological correction programs aimed at improving the psychological and brain functioning of people, emotional freedom techniques, application of emotional reprocessing protocols to improve self regulation, adapted to specific emotional needs, guided neuroplasticity interventions, application of cognitive stimulation techn iques designed to promote neuroplasticity in specific brain areas, character strengths program, implementation of psychological well being management programs based on scientific evidence and personalized neuromanagement education.